Approaches to the Implementation of a Teacher’s Professional Standard: Labor Actions and Systemic Meanings - Uskova, S.A. (Psihologo-pedagogičeskie issledovaniâ, 2020)
The article presents the analysis of the introduction of the professional standard of the teacher (the Standard), and analyzed the risks the formal implementation of the requirements of the Standard situation when the teacher can not organize and build relationships in the framework of functional maps of the profession and driving its operations to implement the desired work functions that does not allow the execution of one of the main functions of the Standard - improve the effectiveness of the educational process. The author presents a theoretical model of modern educational process; the proposed mechanism is a system implementation of the Standard proved the importance of the consideration of the necessary skills and knowledge as the employment action; it shows the variability of implementation of the Standard in accordance with emerging problems in the professional activity of the teacher, the peculiarities of the system of implementation of the Standard by the example of one work function: teaching activities for the implementation of the programmes of primary General education. Testing showed the importance of using the system implementation of the Standard as methodological tools in the process of thinking as a teacher this document. An empirical test of performance was carried out on the basis of an analysis of the final work of 98 students of continuing education courses (primary school teachers). 78% of teachers designed EP, identified the main\ components in it and correlated them with the main labor functions. 83% of teachers switched from formal adherence to the standard to the conscious design of the study program. В статье представлен анализ введения профессионального стандарта педагога (далее — Стандарт), проанализированы риски формального осуществления требований Стандарта, ситуации, когда педагог не может систематизировать и выстроить взаимосвязи в рамках функциональной карты вида профессиональной деятельности и сводит свою деятельность к реализации отдельных требуемых трудовых функций, что не позволяет обеспечить выполнение одной из основных функций Стандарта — повышение результативности образовательного процесса. Автором представлена теоретическая модель современного образовательного процесса (далее — ОП); предложен механизм системной реализации Стандарта; доказана важность рассмотрения необходимых умений и знаний как трудовых действий; показана вариативность реализации Стандарта в соответствии с возникающими проблемами проектирования и реализации ОП в профессиональной деятельности учителя; рассмотрена специфика системного осуществления Стандарта на примере разработки модели трудовой функции «Педагогическая деятельность по реализации программ начального общего образования». Апробация показала эффективность предложенного инструмента в системной реализации Стандарта как методического средства в процессе повышения профессиональной квалификации педагога. Эмпирическая проверка результативности была осуществлена на основе анализа итоговых работ 98 слушателей курсов повышения квалификации (учителя начальных классов). 78% учителей проектировали ОП, выделяли в нем основные компоненты и соотносили их с основными трудовыми функциями. 83% учителей перешли от формального следования стандарту к осознанному проектированию ОП.